The Mediating Role of Innovation Capability in the Relationship between Knowledge Sharing on SMEs’ Performance - Pranowo, Agus Setyo; Dachi, Anugerah; Nasution, Novrihan Leily; Ende, Ende; Hendayana, Yayan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of knowledge sharing, innovation capability on SMEs' Performance. The sample in this study is a shoe business owner in Bogor. The questionnaires were distributed as many as 230 questionnaires, and returned as many as 177 questionnaires so that the sample in this study was 177 respondents. The method used is SEM analysis with AMOS Version 23 software. The results show that there was a positive and significant influence between knowledge sharing on innovation capability. There was a positive and significant effect between knowledge sharing and innovation capability on performance. In the future, the shoe industry in Bogor City needs to improve knowledge sharing and innovation capability in order to improve business performance.